2021
DOI: 10.3390/su132112025
|View full text |Cite
|
Sign up to set email alerts
|

Consumers Purchase Intentions of Green Electric Vehicles: The Influence of Consumers Technological and Environmental Considerations

Abstract: The purpose of the current study is to explore barriers influencing consumers’ intention to adopt sustainable electric vehicles (EV) based on the modified theory of planned behavior (TPB) model. Structural equation modeling (SEM) and confirmatory factor analysis (CFA) were employed to analyze the research model, using 262 valid responses. The findings of the current study explored how attitude (ATT), subjective norm (SN), and perceived behavioral control (PBC) significantly influenced users’ sustainable consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…In addition, social norms refer to how people think and act pro-environmentally [ 72 ]. The reviewed studies present the role of social norms in predicting pro-environmental behavior and changing people’s green behaviors [ 41 , 47 , 53 , 62 , 72 ]. The results indicate that people are significantly influenced by society’s actions regarding pro-environmental issues and the way society presents normality in this context.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, social norms refer to how people think and act pro-environmentally [ 72 ]. The reviewed studies present the role of social norms in predicting pro-environmental behavior and changing people’s green behaviors [ 41 , 47 , 53 , 62 , 72 ]. The results indicate that people are significantly influenced by society’s actions regarding pro-environmental issues and the way society presents normality in this context.…”
Section: Resultsmentioning
confidence: 99%
“…Although in the past, social norms represented one of the most used factors influencing consumers’ environmental behaviors [ 81 ], this concept is still an important one when it comes to making consumers act pro-environmentally [ 41 , 47 , 53 , 62 , 72 , 82 ]. Letting people know how others act regarding the protection of the environment can be the key to how social norms can influence green buying behavior [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PBC, the third variable of the TPB theory, defines the ease or difficulty with which a person may exhibit a specific type of behaviour (Ajzen, 1991). PBC is also the perception of how easy or difficult it is to perform a behaviour (Dutta & Hwang, 2021;Yeğin & Ikram, 2022). Some studies have outlined PBC as an essential determinant of adoption intention, even for electric vehicles.…”
Section: Perceived Behavioural Control (Pcb)mentioning
confidence: 99%
“…First, being emission free and costing less for driving makes electric vehicles an environment friendly product, and it has been suggested in a survey conducted in 2019 that 65.9% of respondents in China prefer an electric vehicle over a conventional vehicle because it is environment friendly [35]. Second, specific constructs on environmental psychology studies are also found to have a close relationship with intention to adopt an electric vehicle, such as environmental concern [36], personal norms [12,31,37] and environmental self-identity [29,38]. Based on the above reasons, the discussion of intention to adopt an electric vehicle would be conducted from pro-environmental behavior perspective.…”
Section: Literature Review 21 Intention To Adopt Electric Vehiclesmentioning
confidence: 99%